2003
DOI: 10.1021/jo035065+
|View full text |Cite
|
Sign up to set email alerts
|

MetAP-2 Inhibitors Based on the Fumagillin Structure. Side-Chain Modification and Ring-Substituted Analogues

Abstract: The preparation of a series of new fumagillin-derived MetAP-2 inhibitors is described. The synthetic approach was designed so as to permit modification of the fumagillin backbone at sites inaccessible through semisynthesis or previously existing total syntheses. An Evans aldolization and a ring-closing metathesis allowed the preparation of a pivotal intermediate which could then be functionalized in various ways using already established or newly developed methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Liotta showed that a non‐complexed, and hence more nucleophilic anion is formed by reduction of diphenyl diselenide by sodium metal, or deprotonation of benzeneselenol with sodium hydride . Pleasingly exposure of the enantioenriched γ‐lactone (+)‐ 36 to phenylselanyl anion prepared by reduction of diphenyl diselenide with sodium hydride allowed reaction at room temperature to give the fully substituted pyrrolidinone 39 after acid base extraction (Scheme ). Reduction of the carboxylic acid in 39 to the corresponding primary alcohol 40 proved problematic with direct reduction using borane resulting in substrate decomposition and attempted reduction of the corresponding mixed anhydride with sodium borohydride resulting in numerous uncharacterized products being formed.…”
Section: Resultsmentioning
confidence: 99%
“…Liotta showed that a non‐complexed, and hence more nucleophilic anion is formed by reduction of diphenyl diselenide by sodium metal, or deprotonation of benzeneselenol with sodium hydride . Pleasingly exposure of the enantioenriched γ‐lactone (+)‐ 36 to phenylselanyl anion prepared by reduction of diphenyl diselenide with sodium hydride allowed reaction at room temperature to give the fully substituted pyrrolidinone 39 after acid base extraction (Scheme ). Reduction of the carboxylic acid in 39 to the corresponding primary alcohol 40 proved problematic with direct reduction using borane resulting in substrate decomposition and attempted reduction of the corresponding mixed anhydride with sodium borohydride resulting in numerous uncharacterized products being formed.…”
Section: Resultsmentioning
confidence: 99%
“…Fumagillin inhibits HUVEC proliferation at low nM concentration, and it has partial or no effect on non-endothelial cells at concentrations up to 1 µM (J. . It was proposed that fumagillin inhibits angiogenesis by covalently binding to the His-231 position of the enzyme MetAP2 (Griffith et al 1997;Sin et al 1997), and this finding provided a starting point for the rational design of fumagillin analogs (Rodeschini et al 2004). …”
mentioning
confidence: 99%
“…Epoxidation of the enone moiety by TBHP in the presence of benzyltrimethylammonium hydroxide (triton B)18 furnished stereoselectively epoxide ( 14 ), in 65% yield for three steps from 13 19. The regioselective opening of the epoxide moiety20 found within 14 was established by PhSeNa (generated in situ from diphenyl diselenide and NaBH 4 ) in 86% yield followed by silylation of 15 with SEMCl, which led to disilyl ether ( 16 ) in 85% yield from 14 (Scheme 1). …”
Section: Resultsmentioning
confidence: 99%